2011
DOI: 10.1016/j.ijid.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical characteristics, and outcome of candidemia: experience in a tertiary referral center in the UK

Abstract: Candidemia continues to be associated with a high mortality. Preventative measures should be targeted against high-risk hospitalized patients, especially those in ICUs, the elderly, and those undergoing major surgery. Local surveillance of candidemia is important to optimize management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
94
3
37

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 24 publications
10
94
3
37
Order By: Relevance
“…This is similar to the incidence rates published by other groups in our country (Colombo et al 2007, França et al 2008, Girão et al 2008, Nucci et al 2010), but consistently higher than studies conducted in the northern hemisphere. Epidemiological studies performed in tertiary care hospitals in Europe and the United States have shown incidence rates ranging from 0.02-1.08 cases per 1,000 hospital admissions (Hajjeh et al 2004, Tortorano et al 2004, Almirante et al 2005, Zilberberg et al 2008, Poikonen et al 2010, Arendrup et al 2011, Das et al 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the incidence rates published by other groups in our country (Colombo et al 2007, França et al 2008, Girão et al 2008, Nucci et al 2010), but consistently higher than studies conducted in the northern hemisphere. Epidemiological studies performed in tertiary care hospitals in Europe and the United States have shown incidence rates ranging from 0.02-1.08 cases per 1,000 hospital admissions (Hajjeh et al 2004, Tortorano et al 2004, Almirante et al 2005, Zilberberg et al 2008, Poikonen et al 2010, Arendrup et al 2011, Das et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of candidaemia continues to be high, with incidence rates ranging from 1.27-2.49 per 1,000 admissions (Colombo et al 2006, França et al 2008, Girão et al 2008, Motta et al 2010, Pereira et al 2010. Conversely, studies undertaken in tertiary hospitals in the United States and several European countries have shown lower incidence rates, ranging from 0.28-0.96 and 0.02-1.08 per 1,000 admissions, respectively (Hajjeh et al 2004, Tortorano et al 2004, Almirante et al 2005, Zilberberg et al 2008, Poikonen et al 2010, Arendrup et al 2011, Das et al 2011 .…”
mentioning
confidence: 99%
“…La incidencia de candidemia en nuestro centro resultó menor a la publicada en estudios epidemiológicos, tanto de países de Latinoamérica como de otros continentes 6,9,10 . Respecto a los datos latinoamericanos reportados por Nucci y cols.…”
Section: Discussionunclassified
“…En su mayoría, la candidemia representó un evento tardío dentro de la tercera semana de hospitalización y más de la mitad de los casos se encontraban en UPC al momento del diagnóstico. Todos estos aspectos son similares a lo antes publicado en la literatura internacional 2,8,10 .…”
Section: Discussionunclassified
“…Currently, other species of this genus have been found to cause an increasing number of cases of candidiasis (Mokaddas et al, 2007;Pereira et al, 2010;Das et al, 2011).…”
Section: Introductionmentioning
confidence: 99%